Water, Sanitation and Hygiene in Nepal and International Travellers’ Travel-Health Experiences - Bhatta, Ramesh; Aryal, Kabita; Thapa, Pramila; Joshi, Kumari Damayanti; Bhatta, Chhavi Raj (Journal of Nepal Health Research Council, 2023)
Background: Tourism is one of the main sectors in Nepal, contributing in its economic growth. It is influenced by various factors including the situation of water, sanitation and hygiene and water, sanitation and hygiene practices. For travelers, poor water, sanitation and hygiene provisions are considered risk factors for different food and water-borne diseases. This study aims to describe the perceptions of international travelers regarding their experiences on WASH facilities or practices, and how it influences their health, and travel experiences. Methods: This is a cross-sectional pilot study conducted among 150 international travelers in Nepal. The travelers were selected conveniently from the Kathmandu valley. The data on different water, sanitation and hygiene related variables, travelers’ health and travel experiences were collected using semi-structured questionnaire. The quantitative data was entered into SPSS for descriptive analysis and qualitative data was transcribed through thematic analysis. Results: Of 150 international travelers, about 2/3rd of the travelers had inadequate perception of water, sanitation and hygiene condition. Nearly 23% of them experienced gastrointestinal symptoms, including diarrhea in the past week during their visit. Among those travelers who experienced gastrointestinal symptoms, 21.4% of them reported of their travel plans being affected. Conclusions: Perception and experience with water, sanitation and hygiene facilities was found inadequate among international travelers visiting Nepal. Such facilities seem to have affected the travelers’ health (nearly a quarter of them experienced gastrointestinal symptoms, including diarrhea) and their travel plan. Hence, this pilot study demonstrates that there is an urgent need to improve the water, sanitation and hygiene facilities in the travel and tourism sector of Nepal. Keywords: Nepal; travelers and travel health; water, sanitation and hygiene